Code Grey: Stained Surgical Instruments and Their Impact on One Canadian Health Authority - Rob Kean, Ron Johnson and Michael Doyle (Law & Governance, 2018)
[This article was originally published in Healthcare Quarterly, 20(3) In 2016, NL's largest RHA was faced with serious challenges stemming from the discovery of stained surgical instruments at its two largest hospitals. This discovery prompted a series of postponed surgeries, an extensive internal mobilization of labour and the purchase of millions of dollars of new equipment. In tackling these challenges, the organization not only acquired a better understanding of its surgical tools, but it also gained renewed appreciation for the resilience of its human resources. By describing this incident and the lessons learned, we hope to offer insight to providers in similar circumstances.
Keywords: stained surgical instruments, surgical tools, process improvement, human resources